On a Vaccination Model for Non-fatal Rare Infectious Diseases; with Emphasis on Rubella in Kuwait - Moussa, M. A. A. (Methods of Information in Medicine, 1979)
An immunization model for non-fatal rare contagious diseases in non-fixed size communities (developing countries) is proposed. It reveals the demographic and epidemiological data needed in a country to decide upon the best strategy of vaccination. The approach is illustrated with reference to rubella in Kuwait population. Comparisons between rubella vaccination strategies of the U.S.A., U.K. and a recently suggested one for Kuwait are carried out.
Keywords: Epidemic Models; Rubella Vaccination Programmes